Estimating Illumination Direction for Augmented Reality in Real-Time by using Low-Cost Sensors - Soulier, Kevin E. (2017)
In recent years, Augmented Reality has become a very popular topic, both as a research and commercial field. This trend has originated with the use of mobile devices as computational core and display. The appearance of virtual objects and their interaction with the real world is a key element in the success of an Augmented Reality software. A common issue in this type of software is the visual inconsistency between the virtual and real objects due to wrong illumination. Although illumination is a common research topic in Computer Graphics, few studies have been made about real time estimation of illumination direction. In this work we present a low-cost approach to detect the direction of the environment illumination, allowing the illumination of virtual objects according to the real light of the ambient, improving the integration of the scene. Our solution is open-source, based on Arduino hardware and the presented system was developed on Android.